MAKNA SASOLAHAN SANGHYANG SAMPAT PADA PURNAMA SASIH KARO DI DESA LEMBONGAN - I Gede Dedy Diana Putra (Genta Hredaya: Media Informasi Ilmiah Jurusan Brahma Widya STAHN Mpu Kuturan Singaraja, 2019)
The Sanghyang Sampat school is a sacred dance that is closely related to the supernatural, scenic, and is believed to help the people of Lembongan Village in the event of natural disasters, infectious diseases, drive out disease outbreaks and others. The Sanghyang Sampat school is also a means to neutralize or protect against the threat of magical power (black magic). Meaning of Sanghyang Sampat School, namely: (1) The Meaning of Bhakti, which is visualized, educates Hindus to be able to surrender themselves with surrender so as to be able to let go of the attachments of life and finally all are absorbed in God's love, (2) The Meaning of Purification, purifying Bhuana Alit and Bhuana Great because this dance is processed through a purification process. With this purification process, it is believed that the Sanghyang Sampat School has purity values and is able to purify the universe and its contents, (3) The Meaning of Balance, the relationship developed between humans and gods, humans and humans, humans and nature, (4) The Meaning of Preservation Culture, Sanghyang Sampat is a product of cultural heritage from the community because the performance is very sacred. In addition, the Sanghyang Sampat Saschool art is a legacy from ancestors who have religious elements.